2020
DOI: 10.21203/rs.3.rs-134630/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effects of Long-Term (7 Years) Adoption of Conservation Agriculture and Nutrient Management Practices on the Soil Properties, System Crop and Water Productivity and Farm Economics of a Maize–Chickpea Rotation 

Abstract: Conservation agriculture (CA)-based practices have been promoted and recouped, as they hold the potential to enhance farm profits besides a consistent improvement in soil properties. The CA-based crop establishment practices (CEP) along with adequate fertilizer inputs in the diversified maize-chickpea rotation (MCR) could be a profitable choice to sustain the crop production of Indo-Gangetic plains in the posterity. Therefore, a seven years' field experiment consisting of three CEP viz., zero till flatbed (ZTF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…This could be explained by the fact that the lack of field preparation led to a decrease in the energy consumption of the CA plots. Most previous research has identified a medium-to long-term impact of conservation tillage strategies on soil quality and crop yield (Pooniya et al, 2020).…”
Section: Energy Budgetingmentioning
confidence: 99%
“…This could be explained by the fact that the lack of field preparation led to a decrease in the energy consumption of the CA plots. Most previous research has identified a medium-to long-term impact of conservation tillage strategies on soil quality and crop yield (Pooniya et al, 2020).…”
Section: Energy Budgetingmentioning
confidence: 99%